PERBANDINGAN PENGARUH ANTARA PMR DAN PENDEKATAN PBM TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Rimadhani, Hikmahtin; Julia, J.; Isrok'atun, I. (Jurnal Pena Ilmiah, 2017)
The background of this research is conducted because there are similarities between Realistic Mathematics Approach (PMR) and Problem-Based Learning approach (PBM) which are a learning approach that leads students to constructivist learning and low mathematical problem solving ability of elementary school students of math class. The aim of this research is to discover the greater influence among PMR, PBM, or conventional approach in improving students' mathematical problem solving ability. The research method used is quasi-experiment with non-equivalent control group design. The populations are all fourth graders in Arjawinangun subdistrict which are in the superior group of academic year 2016/2017. The sampling technique used cluster sampling with three classes required as samples. The result of this study indicates that PBM approach gives greater influence than PMR and conventional approach in improving students' mathematical problem solving ability.